Digital-Based Portfolio Assessment Competence of Early Childhood Educators - Siti Mahriyani Marsegi; Sri Nurhayati; Ansori Ansori; Heris Hendriana (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
In today's era of digital-based learning management, educators must have knowledge and skills in the use of digital technology in teaching and learning activities. This study aims to analyze data on the competence of digital-based portfolio assessment of Early Childhood Care and Education (ECCE) teachers who teach at Kindergarten and Playgroup in the city of Bandung. The research method used was descriptive with a qualitative approach. The research informants included 14 teachers, 3 principals, and 1 vice principal. Data collection techniques used in this study include in-depth interviews, non-participatory observations, documentation studies, and relevant literature. Data analysis techniques used triangulation. The results of the study include: the ECCE educators’ competence of digital-based assessment in Lengkong District, Bandung City, are categorized as low and still needs to be improved. Especially related to the knowledge and skills mastery of digital media assessment tools such as Canva and the like, to support the assessment of students' portfolio in schools. This research recommends the digital-based portfolio assessment of ECCE educators competence improvement both through continuous training and also through the establishment of a joint learning forum.